Analysis of the Solar Pyrolysis of a Walnut Shell: Insights into the Thermal Behavior of Biomaterials - Arturo Aspiazu-Méndez; Nidia Aracely Cisneros-Cárdenas; Carlos Pérez-Rábago; Aurora M. Pat-Espadas; Fabio Manzini-Poli; Claudio A. Estrada (Energies, 2024)
The state of Sonora, Mexico, stands as one of the leading producers of pecan nuts in the country, which are commercialized without shells, leaving behind this unused residue. Additionally, this region has abundant solar resources, as shown by its high levels of direct normal irradiance (DNI). This study contributes to research efforts aimed at achieving a synergy between concentrated solar energy technology and biomass pyrolysis processes, with the idea of using the advantages of organic waste to reduce greenhouse gas emissions and avoiding the combustion of conventional pyrolysis through the concentration of solar thermal energy. The objective of this study is to pioneer a new experimental analysis methodology in research on solar pyrolysis reactors. The two main features of this new methodology are, firstly, the comparison of temperature profiles during the heating of inert and reactive materials and, secondly, the analysis of heating rates. This facilitated a better interpretation of the observed phenomenon. The methodology encompasses two different thermal experiments: (A) the pyrolysis of pecan shells and (B) the heating–cooling process of the biochar produced in experiment (A). Additionally, an experiment involving the heating of volcanic stone is presented, which reveals the temperature profiles of an inert material and serves as a comparative reference with experiment (B). In this experimental study, 50 g of pecan shells were subjected to pyrolysis within a cylindrical stainless-steel reactor with a volume of 156 cm3, heated by concentrated radiation from a solar simulator. Three different heat fluxes were applied (234, 482, and 725 W), resulting in maximum reaction temperatures of 382, 498, and 674 °C, respectively. Pyrolysis gas analyses (H2, CO, CO2, and CH4) and characterization of the obtained biochar were conducted. The analysis of heating rates, both for biochar heating and biomass pyrolysis, facilitated the identification, differentiation, and interpretation of processes such as moisture evaporation, tar production endpoint, cellulosic material pyrolysis, and lignin degradation. This analysis proved to be a valuable tool as it revealed heating and cooling patterns that were not previously identified. The potential implications of this tool would be associated with improvements in the design and operation protocols of solar reactors.